The siege of Dalmatovsky monastery during the peasant unrest of 1842 - Igor Menshchikov; Timofei Pavlutckikh (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2022)
The article deals the peasant unrest of 1842–1843, known as the potato riots. The epicenter of the riots of 1842 was in the Trans-Ural uezdes (districts) of the Perm Governorate (Kamyshlovsky and Shadrinsky). The peasants seized the volost boards and churches, demanded from the rural authorities and the clergy to issue them a "sales charter", according to which they were transferred to serfs. Fearing the anger of the crowd, several country authorities fled to the Dalmatov Dormition Monastery to find refuge outside its walls. However, peasants from the surrounding villages began to gather in the town of Dalmatovo, they captured the Dalmatian volost head and the clerk and demanded that they be given a "sales charter" under the threat of torture. At this time, the treasurer of the monastery, Hieromonk Nicholas, ordered the gates of the monastery to be locked and threatened the rebels that he would fire a cannon. Then, as part of a religious procession, he proceeded to the volost administration house and freed the captive country authorities. After that, he, not meeting resistance, returned with them to the monastery. These events were portrayed by some Soviet historians, such as Nicolay Druzhinin, Sergey Tokarev, as a heroic siege of the Dalmatov monastery. However, an analysis of archived and published sources demonstrates that there was no siege in fact, the peasants were not going to seize the monastery and did not interfere with the movement from it, and the firing from the monastery was carried out with blank charges. When the military detachments arrived the next day, most of the peasants fled, several dozen were arrested without resistance and put on trial. Thus, we are dealing with a historiographical myth based on soviet ideology and an uncritical attitude towards the sources and works of other historians.